Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1128/jb.175.14.4325-4334.1993
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Holliday intermediates in recombination and DNA repair: indirect suppression of ruvA, ruvB, and ruvC mutations

Abstract: The ruvA, ruvB, and ruvC genes of Escherichia coli provide activities that catalyze branch migration and resolution of Holliday junction intermediates in recombination. Mutation of any one of these genes interferes with recombination and reduces the ability of the cell to repair damage to DNA. A suppressor of ruv mutations was identified on the basis of its ability to restore resistance to mitomycin and UV light and to allow normal levels of recombination in a recBC sbcBC strain carrying a Tn10 insertion in ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
139
0
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(149 citation statements)
references
References 47 publications
(58 reference statements)
5
139
0
3
Order By: Relevance
“…Genetic analyses indicate that RuvC resolvase plays a defined role in processing recombination and repair intermediates (7)(8)(9)(10)(11). In vitro studies confirm that RuvC specifically interacts with and resolves Holliday junctions by endonucleolytic cleavage (12,13).…”
mentioning
confidence: 78%
“…Genetic analyses indicate that RuvC resolvase plays a defined role in processing recombination and repair intermediates (7)(8)(9)(10)(11). In vitro studies confirm that RuvC specifically interacts with and resolves Holliday junctions by endonucleolytic cleavage (12,13).…”
mentioning
confidence: 78%
“…The following alleles were transduced into FC36 by selection for the indicated drug resistances and screening for increased sensitivity to UV light: recA938:: Tn9200 (45), ⌬(ruvAC) 65, eda57::Cam (18,35), and recG258::dTn10Kan (30). The Lac Ϫ Tet s episome was then mated into these strains by selection for proline prototrophy (Pro ϩ ).…”
Section: Methodsmentioning
confidence: 99%
“…Both Tet s alleles were recessive to Tet r , indicating that they contain mutations in the structural gene for tetracycline resistance, tetA. The two tetA alleles were amplified (the 5Ј primer had the sequence of bp 1574 to 1596, and the 3Ј primer was complementary to bp 2820 to 2838 of the TRN10TETR locus [GenBank accession number J01830]) and sequenced with an ABI 373A sequencer.The following alleles were transduced into FC36 by selection for the indicated drug resistances and screening for increased sensitivity to UV light: recA938:: Tn9200 (45), ⌬(ruvAC) 65, eda57::Cam (18,35), and recG258::dTn10Kan (30). The Lac Ϫ Tet s episome was then mated into these strains by selection for proline prototrophy (Pro ϩ ).…”
mentioning
confidence: 99%
“…After branch migration, a dimer of RuvC resolves the HJ by making two sequence-specific symmetrical cuts, producing either patched or spliced linear products (4 -6). Genetic studies showed that RuvC cannot function in vivo in the absence of RuvAB (7,8), and it has been proposed that an RuvABC complex, known as the resolvasome, allows RuvC to scan for cleavable sequences (3, 9 -11). RuvA binds to HJs in vitro as one tetramer (complex I) or two tetramers that sandwich the junction (complex II) in a concentration-dependent manner; however, it is not clear whether the RuvAB complex contains one or two tetramers of RuvA in vivo (12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%